Clinical Validation of the Impact of Branch Stent Extension on Hemodynamics in ISF-TEVAR Involving LSA Reconstruction - Hu, Jiateng; Li, Fengshi; Qiu, Peng; Wu, Xiaoyu; Pu, Hongji; Zhao, Zhen; Qin, Jinbao; Liu, Guang; Jin, Shanliang; Lu, Xinwu; Liu, Xiaobing (Frontiers in Cardiovascular Medicine, 2022)
Background: The study of hemodynamics regarding TEVAR is helpful to improve the surgical efficacy. Objective: Correlations between hemodynamic changes and branch stent extension length and interference factors for branch stent extension length of in situ fenestration thoracic endovascular aortic repair (ISF-TEVAR) involving the left subclavian artery (LSA) were evaluated. Materials and methods: This study retrospectively analyzed 196 patients with Stanford type B aortic dissection who received in situ laser fenestrated thoracic endovascular aortic repair with LSA fenestration from April 2014 to March 2021. Branch stent extension to the main stent graft was evaluated by CTA. The indication for the hemodynamic change of LSA was defined as a 20 mmHg interbrachial systolic pressure difference. The factors affecting the extension of the branch stent were also evaluated. Results: All patients underwent ISF-TEVAR with LSA fenestration, and there was no recurrence during the follow-up. The mean length of the branch stent extension was 10.37±0.34 mm, which was used to divide the patients into long and short groups. Asymptomatic hemodynamic changes (defined as a 20 mmHg interbrachial systolic pressure difference) in LSA were observed in 61 patients undergoing ISF-TEVAR involving LSA fenestration. The Spearman correlation analysis showed extension length of branch stent greater than 1.5 cm elevated the risk of hemodynamic changes. Conclusion: Overall, we conclude that branch stent extension length greater than 1.5 cm induced LSA hemodynamic changes. Appropriate shortening of the stent extension length can improve the curative effect of ISF-TEVAR, especially when faced with a type II/III aortic arch and stent angles of less than 30 degrees.